2015
DOI: 10.1038/nrn3978
|View full text |Cite
|
Sign up to set email alerts
|

Immune mediators in the brain and peripheral tissues in autism spectrum disorder

Abstract: Increasing evidence points to a central role for immune dysregulation in autism spectrum disorder (ASD). Several ASD risk genes encode components of the immune system and many maternal immune system-related risk factors — including autoimmunity, infection and fetal reactive antibodies — are associated with ASD. In addition, there is evidence of ongoing immune dysregulation in individuals with ASD and animal models of this disorder. Recently, several molecular signalling pathways have been identified that link … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
358
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 414 publications
(370 citation statements)
references
References 265 publications
(286 reference statements)
8
358
1
3
Order By: Relevance
“…Immune dysfunction (18,(20)(21)(22) and inflammation of the brain (23)(24)(25) are now invoked in the pathogenesis of ASD. However, the stimuli that promote these inflammatory processes in the brain are presently unknown.…”
mentioning
confidence: 99%
“…Immune dysfunction (18,(20)(21)(22) and inflammation of the brain (23)(24)(25) are now invoked in the pathogenesis of ASD. However, the stimuli that promote these inflammatory processes in the brain are presently unknown.…”
mentioning
confidence: 99%
“…Postmortem studies using brain specimens from depressed suicide victims have revealed epigenetic modifications (methylation abnormalities) in the promoter region of BEGAIN, a gene associated with PSD95 expression (Nagy et al, 2015). In addition, PSD95 engulfment by microglia can lead to excessive complement activation and pruning (Estes and McAllister, 2015). Although specific information is still lacking, it would be tempting to speculate that the movement and clustering of AMPA and NMDA proteins and their binding to stargazin or nitric oxide synthase within the PSD95 complex might be altered during inflammatory activation in mood disorders.…”
Section: Synaptogenesis Gliotransmission and Circuit Integrationmentioning
confidence: 99%
“…The clustering and location of ionotropic receptors within the postsynaptic membrane varies across contexts and time points, and regulates the balance between activation and desensitization of AMPA and NMDA receptors, and thus has the potential to decrease neuroplasticity and increase signaling disarray (Allam et al, 2015;Allam et al, 2012;Ma et al, 2014). PSD95 function is controlled by immune activity in the glial cells such as astrocytes and microglial cells (Torres-Platas et al, 2014b; Torres-Platas et al, 2011) during physiological (normal development) and pathological contexts (Estes and McAllister, 2015). For example, prenatal immune activation using poly(I:C), a preclinical model of prenatal viral exposure implicated in schizophrenia and autism spectrum disorders resulted in pronounced decreases of PSD95 in hippocampal regions associated with prominent behavioral changes (Giovanoli et al, 2016).…”
Section: Synaptogenesis Gliotransmission and Circuit Integrationmentioning
confidence: 99%
“…Further, twin and family studies indicate that both genetic and environmental factors, as well as their interplay, influence ASD etiology. [29][30][31][32] Age and gender bias, in combination with limited control over genetic and environmental confounders, are likely to have contributed to earlier mixed findings of RS connectivity in ASD. To this end, discordant monozygotic (MZ) twin pair designs provide excellent methodological control over genetic as well as shared environmental factors, including age, gender and other possible confounding variables such as family background and parental age.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of our aim to investigate SN and DMN brain connectivity, we extracted functional MRI signal intensity time courses from four ROIs (radius 10 mm) encompassing core hubs within the DMN (PCC [ − 6, − 44,34] and vmPFC [ − 2, 38, − 12]) and the SN (right AI = rAI [39, 23, − 4] and ACC [6,24,32]). The selection of coordinates was based on the peaks of activity yielded by a previous Independent Component Analysis study conducted in typically developed children and adults.…”
Section: Selection Of Regions Of Interestmentioning
confidence: 99%